2009
DOI: 10.1348/000709908x313758
|View full text |Cite
|
Sign up to set email alerts
|

Increase in counselling communication skills after basic and advanced microskills training

Abstract: The microcounseling method is very effective on the level of separate microskills. However, students perform better on the basic skills than on the advanced skills. More training seems to be needed in the latter to achieve the same level of mastery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
21
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 20 publications
4
21
0
2
Order By: Relevance
“…For example, one study conducted in 18 first- and second-year medical students with no previous exposure to transurethral resection of prostate in the operating room, showed that for acquisition of transurethral resection skills, task deconstruction is superior to full-task training alone 10. Kuntze et al also demonstrated that microskills training in the counseling communication domain is a very effective method 6. Our findings in this study are compatible with the aforementioned studies.…”
Section: Discussionsupporting
confidence: 90%
“…For example, one study conducted in 18 first- and second-year medical students with no previous exposure to transurethral resection of prostate in the operating room, showed that for acquisition of transurethral resection skills, task deconstruction is superior to full-task training alone 10. Kuntze et al also demonstrated that microskills training in the counseling communication domain is a very effective method 6. Our findings in this study are compatible with the aforementioned studies.…”
Section: Discussionsupporting
confidence: 90%
“…Students in the study exhibited an increase in reflection of client feeling (conveying empathy), as well as a decrease in the use of closed-ended questions. Kutze, van der Molen, and Born (2009) found that psychology students who were taught this method exhibited similar counseling behaviors, especially in terms of those associated with empathy. In a small study of academic advisors, Bartnett, Roach, and Smith (2006) found that learning the microskills associated with attending behavior strengthened advisor-advisee relationships.…”
Section: The Microskills Modelmentioning
confidence: 94%
“…minimal encouragement; asking questions) and advanced (e.g. confrontation, positive relabeling) skills (Kuntze et al 2009). Another tool-'applied behavior analysis' (Alberto and Troutman 1999) is a good example of a structured, process-oriented scheme of action in which practitioners identify a problem and through gradual providing of reinforcement help reduce e.g.…”
Section: Tools Professionals Usementioning
confidence: 99%